2019
DOI: 10.1101/565333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Developmental Recovery of Impaired Multisensory Processing in Autism and the Cost of Switching Sensory Modality

Abstract: 11Children with autism spectrum disorder (ASD) are often impaired in their ability to cope with and process 12 multisensory information, which may contribute to some of the social and communicative deficits that 13 are prevalent in this population. Amelioration of such deficits in adolescence has been observed for 14 ecologically-relevant stimuli such as speech. However, it is not yet known if this recovery generalizes to 15 the processing of nonsocial stimuli such as more basic beeps and flashes, typically us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 128 publications
(236 reference statements)
3
11
0
Order By: Relevance
“…Similar SIFI perception has been reported between adults diagnosed with ASD and controls (Keane et al, 2010;van Der Smagt et al, 2007), although this may be specific to fission than fusion effects (Bao et al, 2017). It has been suggested that individuals diagnosed with ASD undergo a developmental delay in sensory processing, with multisensory abilities reaching age-normal levels by mid-twenties (Crosse et al, 2019). Findings from studies using the SIFI therefore support this conclusion.…”
Section: Autism Spectrum Disordersupporting
confidence: 67%
“…Similar SIFI perception has been reported between adults diagnosed with ASD and controls (Keane et al, 2010;van Der Smagt et al, 2007), although this may be specific to fission than fusion effects (Bao et al, 2017). It has been suggested that individuals diagnosed with ASD undergo a developmental delay in sensory processing, with multisensory abilities reaching age-normal levels by mid-twenties (Crosse et al, 2019). Findings from studies using the SIFI therefore support this conclusion.…”
Section: Autism Spectrum Disordersupporting
confidence: 67%
“…While our findings suggest superior perceptual processing in ASD, in line with theories of enhanced local processing (Happé and Frith 2006 ; Mottron et al 2006 ), there are studies to suggest that perceptual processing is impaired in ASD (Haigh et al 2015 ), and particularly multisensory integration (Stevenson et al 2014 ; Noel et al 2018 ; Crosse et al 2019 ). However, it is important to point out that work on multisensory integration in ASD differs considerably in terms of task requirements from an inattentional deafness task used here: the former typically results in enhanced perception of one stimulus in the presence of a stimulus in a different modality, while the latter is a selective attention task in which the additional auditory CS does not facilitate processing of the visual stimulus, or vice versa.…”
Section: Discussionsupporting
confidence: 85%
“…Likewise, the predictions of the race model were “violated” for asynchronies ≤70 ms. Both of these analyses suggest that observers experience benefits in audiotactile processing for TIW of ≤70 ms, though some of these reaction time differences may reflect modality switching costs as a result of random ordering the auditory, tactile and audiotactile conditions (Shaw et al, 2020; Crosse, Foxe, & Molholm, 2019).…”
Section: Discussionmentioning
confidence: 99%